Reduced ErbB4 Expression in Immune Cells of Patients with Relapsing Remitting Multiple Sclerosis. (12th September 2011) - Tynyakov-Samra, Evgenia; Auriel, Eitan; Levy-Amir, Yifat; Karni, Arnon
Abstract : Background. There is an insufficient remyelination in the lesions of multiple sclerosis (MS). One of the factor that was found to promote remyelination is neuregulin-1 which is the ligand of ErbB4. Immune cells have been implicated in neurogenesis and oligodendrogenesis. Aims. We studied the expression of ErbB4 in the immune cells of patients with relapsing remitting (RR) multiple sclerosis (MS) and healthy controls. Methods. ErB4 expression in immune cells was studied by flow cytometry without stimulation or with stimulation with anti-CD3 and anti-CD28 monoclonal antibodies or in the presence of interferon-g or TNF- α as well as by immunoprecipitation and Western blot, and its mRNA was studied by real-time PCR. Results. We found reduced levels of ErbB4 in the total PBMCs and in T cells, monocytes, and B cells of RR MS patients. Similarly, the ErbB4 RNA levels were reduced in the immune cells of patients with RR-MS. Stimulation via CD3 and CD28 significantly upregulated the expression of ErbB4 on immune cells healthy individuals. This effect was weaker in the patients group. Conclusion. ErbB4 may play a role in the proliferation of oligodendrocyte progenitor cells, differentiation of oligodendrocytes, and remyelination, and, therefore, the reduced ErbB4 expression in immune cells of patients with RR-MS may contribute to insufficient remyelination that occurs in the disease.